PENGARUH KEMAJUAN TEKNOLOGI, MINAT INVESTASI, DAN PENGETAHUAN INVESTASI TERHADAP KEPUTUSAN INVESTASI DI PASAR MODAL (STUDI PADA MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS MATARAM) - INDRAWATI, WIWIK; CAHYANINGTYAS, SUSI RETNA (GANEC SWARA, 2024)
This study aims to analyze the effect of technological progress, investment interest, and investment knowledge on investment decisions in the capital market. This study uses associative research using a quantitative approach. The data in the study is primary data obtained through distributing questionnaires to 262 respondents who are students of the Accounting Department of Mataram University. The data analysis technique in this study was carried out using the Partial Least Square (PLS) method. After testing, the results of this study indicate that Technological Progress, Investment Interest, and Investment Knowledge have a significant effect on investment decisions in the Capital Market. This research supports the Theory of planned behavior (TPB) theory in explaining the factors that influence investment decisions. The implications of the results of this study can be used as literature or references for accounting students regarding investment decisions by considering technological progress, investment interest, and investment knowledge